Henry Foxall's journals, 1816-1817 - Donovan, Jane, 1956- author. Link
1 online resource (190 pages)
Keywords: This book introduces four journals that Henry Foxall (1758-1823) kept during a trip to the British Isles in 1816-1817. It provides unique primary source material, extensively annotated for clarity and context. Foxall's journals offer an eyewitness account of Methodist embourgeoisement and institutionalization as they were occurring. They also provide some insight into the developing differences between American and British Methodism. The journals contain information on recent technological innovations of the British Industrial Revolution and recount Foxall's interactions with a number of prominent persons, both in British Methodism and outside it. Because of Foxall's close relationship with Francis Asbury, his status as an insider at the highest levels of American Methodism, and his clear understanding of the British Methodism in which he was raised, converted, and first licensed as a local preacher, his perspective is well-informed and unique.